Morphological, thermal and bioactivity evaluation of electrospun PCL/β-TCP fibers for tissue regeneration - Siqueira,Lilian de (2019)
Abstract Electrospinning is a simple and low-cost way to fabricate fibers. Among the various polymers used in electrospinning, polycaprolactone (PCL) stands out due to its excellent biodegradability and biocompatibility. However, PCL has some limitations such as low bioactivity, hydrophobic surface, and long in vivo degradation. Calcium phosphate ceramics have been recognized as an attractive biomaterial. They are bioactive and osteoinductive, and some are even quite biodegradable. Different contents of particles of beta-tricalcium phosphate (β-TCP) were incorporated in polymer matrix to form fibers of PCL/β-TCP composites by electrospinning for possible application in tissue regeneration. The presence of β-TCP particles promoted some changes in the thermal properties of the fibers. The immersion of PCL/β-TCP 8 wt-% fibers in simulated body fluid (SBF) caused the formation of a denser and homogeneous apatite layer on its surface.